Association between AXL, Hippo Transducers, and Survival Outcomes in Male Breast Cancer. Issue 8 (3rd March 2017) - Di Benedetto, Anna; Mottolese, Marcella; Sperati, Francesca; Ercolani, Cristiana; Di Lauro, Luigi; Pizzuti, Laura; Vici, Patrizia; Terrenato, Irene; Shaaban, Abeer M.; Humphries, Matthew P.; Sundara‐Rajan, Sreekumar; Barba, Maddalena; et al.
Abstract : Male breast cancer (MBC) is an uncommon malignancy. We have previously reported that the expression of the Hippo transducers TAZ/YAP and their target CTGF was associated with inferior survival in MBC patients. Preclinical evidence demonstrated that Axl is a transcriptional target of TAZ/YAP. Thus, we herein assessed AXL expression to further investigate the significance of active TAZ/YAP‐driven transcription in MBC. For this study, 255 MBC samples represented in tissue microarrays were screened for AXL expression, and 116 patients were included. The association between categorical variables was verified by the Pearson's Chi‐squared test of independence (2‐tailed) or the Fisher Exact test. The relationship between continuous variables was tested with the Pearson's correlation coefficient. The Kaplan–Meier method was used for estimating survival curves, which were compared by log‐rank test. Factors potentially impacting 10‐year and overall survival were verified in Cox proportional regression models. AXL was positively associated with the TAZ/CTGF and YAP/CTGF phenotypes ( P = 0.001 and P = 0.002, respectively). Patients with TAZ/CTGF/AXL‐ or YAP/CTGF/AXL‐expressing tumors had inferior survival compared with non‐triple‐positive patients (log rank P = 0.042 and P = 0.048, respectively). The variables TAZ/CTGF/AXL and YAP/CTGF/AXL were adverse factors for 10‐year survival in the multivariate Cox models (HR 2.31, 95%CI:1.02–5.22, P = 0.045, and HR 2.27, 95%CI:1.00–5.13, P = 0.050). Nearly comparable results were obtained from multivariate analyses of overall survival. The expression pattern of AXL corroborates the idea of the detrimental role of TAZ/YAP activation in MBC. Overall, Hippo‐linked biomarkers deserve increased attention in this rare disease. J. Cell. Physiol. 232: 2246–2252, 2017. © 2016 Wiley Periodicals, Inc. Abstract : (1) The expression pattern of AXL corroborates the idea of TAZ/YAP activation in male breast cancer; (2) patients whose tumors had the TAZ/CTGF/AXL and YAP/CTGF/AXL molecular backgrounds experienced adverse survival outcomes compared with their negative counterparts.